2020
DOI: 10.1136/bmjdrc-2020-001261
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of weight-based insulin titration (WIT) and glucose-based insulin titration using basal-bolus algorithm in hospitalized patients with type 2 diabetes: a multicenter, randomized, clinical study

Abstract: IntroductionSubcutaneous administration of insulin is the preferred method for achieving glucose control in non-critically ill patients with diabetes. Glucose-based titration protocols were widely applied in clinical practice. However, most of these algorithms are experience-based and there is considerable variability and complexity. This study aimed to compare the effectiveness and safety of a weight-based insulin titration algorithm versus glucose-based algorithm in hospitalized patients with type 2 diabetes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 38 publications
1
0
0
Order By: Relevance
“…Intriguingly, the implementation of BBI itself resulted in superior glycemic control regardless of insulin titration strategies; insulin titration guided by an expert endocrinologist in a tertiary hospital was comparable to titration by structured protocol in terms of efficacy and safety. This is consistent with recent studies that also suggested comparable efficacy of various BBI treatment algorithms that are tailored to individual patients [41][42][43][44][45]. However, the retrospective nature of this study could not distinguish the patients who were genuinely treated with conventional BBI from those apparently treated with conventional methods but were in fact performed by resident physicians who were accustomed to the RABBIT2 protocol.…”
Section: Discussionsupporting
confidence: 88%
“…Intriguingly, the implementation of BBI itself resulted in superior glycemic control regardless of insulin titration strategies; insulin titration guided by an expert endocrinologist in a tertiary hospital was comparable to titration by structured protocol in terms of efficacy and safety. This is consistent with recent studies that also suggested comparable efficacy of various BBI treatment algorithms that are tailored to individual patients [41][42][43][44][45]. However, the retrospective nature of this study could not distinguish the patients who were genuinely treated with conventional BBI from those apparently treated with conventional methods but were in fact performed by resident physicians who were accustomed to the RABBIT2 protocol.…”
Section: Discussionsupporting
confidence: 88%